MENINGKATKAN KEMAMPUAN MEMBACA CEPAT MELALUI TEKNIK SKIMMING PADA MATERI CERPEN DI KELAS V SDN 4 BANDA ACEH - Cut Fitri Nurdian; Mahmud, Teuku; Rahmi, Regina (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2026)
Reading is one of the most essential language skills as it forms the foundation for mastering other language skills. Therefore, effective instructional techniques are needed to improve students’ speed reading ability. This study aimed to determine the effect of the skimming technique on the speed reading ability of fifth-grade students at SDN 4 Banda Aceh in short story material. This research employed a quantitative approach using an experimental method with a One Group Pretest–Posttest Design. The subjects of the study were 21 students. Data were collected through tests (pre-test and post-test) and observation sheets of teacher and student activities.The results showed that the mean score of the pre-test was 39.67 and increased to 81.29 in the post-test, with an improvement of 41.62 points. The Shapiro-Wilk normality test indicated that the data were normally distributed, with significance values of 0.086 for the pre-test and 0.078 for the post-test (> 0.05). The Paired Sample t-Test obtained a significance value (Sig. 2-tailed) of 0.000 (< 0.05), indicating a significant difference before and after the implementation of the skimming technique. Observation results also revealed improvements in students’ participation, focus, and reading fluency during the learning process. Based on these findings, it can be concluded that the implementation of the skimming technique significantly improves the speed reading ability of fifth-grade students at SDN 4 Banda Aceh in short story material. It is recommended that teachers apply the skimming technique as an alternative reading strategy, students practice independently, and future researchers expand the study with larger samples and broader variables